Determination of Heavy Metal Accumulation in Milk and Their Packaging Materials and Statistical Analysis - Kaya, Tuğba Nur; Zurnacı, Merve; Şener, İzzet (Journal of Engineering Technology and Applied Science, 2024)
Heavy metal accumulation occurs when foods and food contact materials contain excessive amounts of heavy metals. Heavy metal accumulation in foods can risk public health and cause diseases. Therefore, the concentration of heavy metals in food and packaging materials is an important parameter that needs to be analyzed. This study aimed to detect heavy metal accumulation in food and packaging materials. For this purpose, milk, which has an essential place among foods, was chosen. Products of 10 different milk brands used commercially today were supplied. Within the scope of heavy metal analyses, Lead (Pb), Arsenic (As), Cadmium (Cd), Iron (Fe), Manganese (Mn), Zinc (Zn), Copper (Cu), Aluminum (Al), Cobalt (Co) and Nickel (Ni) elements were determined. Pre-treatment of the samples was carried out using the efficient microwave method to ensure minimal sample loss through rapid thawing. Heavy metal analysis was then carried out using the widely used ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometer) device, a widespread technique in current practice. The range of heavy metal concentrations in all packaging samples were: Al (1.219–2.578), As (1.078–1.522), Co (0.219–0.239), Fe (0.862–81.440), Pb (1.784–2.170), Mn (0.042–1.884), Ni (0.782–9.758, Zn (1.814–2.522) mg/kg. Heavy metal concentrations in all packaging samples were found Al (51267.00–71601.25), As (31.626–42.371), Cd (1.035–1.209), Co (0.775–1.167), Cu (4.921–44.839), Fe (259.615–463.182), Pb (24.386–26.668), Mn (4.301–59.599), Ni (6.065–7.943), Zn (5.324–8.763) mg/kg. The heavy metals with the highest concentration among packaging materials are Al and Fe, followed by As and Pb. Additionally, the correlation between milk and its packaging samples were presented using SPSS.
Keywords: Material Characterization; Malzeme Karekterizasyonu; Milk; food packaging; microwave; heavy metal accumulation; inductively coupled plasma–optical emission spectrometry (ICP-OES); 2. Zero hunger